2018
DOI: 10.1007/s11356-017-1165-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of selenium and selenium nanoparticles with reference to acute toxicity, biochemical attributes, and histopathological response in fish

Abstract: Recent studies have demonstrated that selenium (Se) and selenium nanoparticles (Se-NPs) exhibited toxicity at a higher concentration. The lethal concentration of Se and Se-NPs was estimated as 5.29 and 3.97 mg/L at 96 h in Pangasius hypophthalmus. However, the effect of different definite concentration of Se (4.5, 5.0, 5.5, and 6.0 mg/L) and Se-NPs (2.5, 3.0, 3.5, and 4.0 mg/L) was decided for acute experiment. Selenium and Se-NPs alter the biochemical attributes such as anti-oxidative status [catalase (CAT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 58 publications
4
55
1
1
Order By: Relevance
“…The higher additive concentration of nano-selenium (3.97 mg/kg or more than 10 mg/kg) exerted a toxic effect. 52,53 Based on the reported concentrations of nano-selenium displaying promoting or toxic effects, four different additive amounts of PSP-SeNPs were designed to investigate their promoting or possible toxic effects on tilapia. However, in the present study, although the lower concentration of PSP-SeNPs supplement (0.5 mg/kg) exhibited the best growth-promoting effects on tilapia, the higher concentration of PSP-SeNPs (4.5 mg/kg) also showed growth-promoting effects during the whole experiment, indicating a wider range of safe dosage and better biocompatibility of PSP-SeNPs.…”
Section: Effects Of Psp-senps On Tilapia Growth Performancementioning
confidence: 99%
“…The higher additive concentration of nano-selenium (3.97 mg/kg or more than 10 mg/kg) exerted a toxic effect. 52,53 Based on the reported concentrations of nano-selenium displaying promoting or toxic effects, four different additive amounts of PSP-SeNPs were designed to investigate their promoting or possible toxic effects on tilapia. However, in the present study, although the lower concentration of PSP-SeNPs supplement (0.5 mg/kg) exhibited the best growth-promoting effects on tilapia, the higher concentration of PSP-SeNPs (4.5 mg/kg) also showed growth-promoting effects during the whole experiment, indicating a wider range of safe dosage and better biocompatibility of PSP-SeNPs.…”
Section: Effects Of Psp-senps On Tilapia Growth Performancementioning
confidence: 99%
“…Selenium (Se) is a key microelement for creatures, which is closely related to a series of major metabolic pathways such as anti-oxidant systems, thyroid hormone metabolism, growth modulation and immune function (Stranges et al 2006;Kumar et al 2018;Xia et al 2018). It has also been reported that Se deficiency (< 40 μg/day) can lead to many diseases, while excessive intake will cause Se poisoning (> 400 μg/day) (Gore et al 2010;Vogel et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [48] described a greater toxicity of SeNPs in comparison with Se IV in the fish Oryzias latipes . Kumar et al [47] reported that the toxicity of SeNPs depends on their concentration, in this case documenting toxic effects on the fish species Pangasius hypophthalmus . Further research is needed to arrive at conclusive evidence for the toxicity level of SeNPs produced by S. bentonitica .…”
Section: Resultsmentioning
confidence: 95%
“…Thus, the production of Se nanospheres by S. bentonitica would be beneficial within a geodisposal system. Notwithstanding, there are considerable uncertainties about the toxicity of SeNPs compared to their soluble oxidized forms, according to some studies [47,48]. Li et al [48] described a greater toxicity of SeNPs in comparison with Se IV in the fish Oryzias latipes .…”
Section: Resultsmentioning
confidence: 99%